Underpotential Deposition Preparation of Pt‐loading AuNPs/Reduced Graphene Oxide and Its Catalytic Detection of Catechol. Issue 11 (24th October 2016) - Wang, Cong; Guo, Zhihua; Zhang, Li; Zhang, Na; Zhang, Keying; Fei, Bailu; Wang, Hongyan; Xu, Jigui; Shi, Hongwei; Qin, Miao; Ren, Lei; Wu, Xingxing
Abstract: Ultralow Pt‐loading Au nanoparticles have been fabricated on the surface of reduced graphene oxide (RGO) by using underpotential deposition (UPD) monolayer redox replacement process. The Pt/Au/RGO modified electrode exhibits an excellent electrocatalytic activity toward catechol and hydroquinone. Under the optimized condition, the separation of peak‐to‐peak between hydroquinone and catechol is 197 mV, which is wide enough to distinguish the isomers of benzenediol. Catechol is detected by the Pt/Au/RGO/GCE with a low detection limit in the presence of hydroquinone. Abstract : Ultralow Pt‐loading Au nanoparticles have been fabricated on the surface of reduced graphene oxide (RGO) by using underpotential deposition (UPD) monolayer redox replacement process. The Pt/Au/RGO modified electrode exhibits an excellent electrocatalytic activity toward catechol and hydroquinone.